Mini Review: The Potential of Piperine in Black Pepper in Improving Brain Work - Dandy Dewanto P; Putri Kinanthi; Naila Sistharani; Nurul Aqidatul; Dewi Yuniasih (Ahmad Dahlan Medical Journal, 2021)
This study aims to determine the effect of piperine as an antidepressant and the potential to improve brain cognitive function. Researchers conducted a literature review related to piperine's potential for brain work using databases such as PubMed, Google Scholar, Cochrane Library. Search the relevant research literature using the keywords "Piperine in black pepper" or "piperine and brain effects". One of our conclusions is that piperine's cognitive-enhancing effects may occur in part through its cytoprotective and AChE inhibitory effects in the hippocampus.